Social anxiety mediates between victimization experiences and internet addiction among adolescents: results from propensity score matching - Wu, Jianwei; Wang, Hui; Li, Xiang; Van, Iat Kio; Xie, Xuebin; Pang, Ching Han (Frontiers in Psychology, 2024)
Background: Previous research has indicated that Victimization Experiences (VE) may be linked to a heightened likelihood of developing psychological symptoms and Internet Addiction (IA) among adolescents. However, the precise mechanism through which VE contributes to IA in adolescents remains uncertain. This study aimed to investigate whether Social Anxiety (SA) serves as a mediation between VE and IA, utilizing the framework of General Strain Theory.A cross-sectional survey among 11 middle schools or high schools in Macao was conducted from October to December 2022. Respondents in the victimized group and non-victimized group were 1:1 paired using Propensity Score Matching (PSM) to control the potential confounding factors.Results: A total of 1089 questionnaires were valid for analysis and 311 pairs were generated through PSM. Respondents in the victimized group reported significantly higher IA than those in nonvictimized group (23.5% vs. 12.5%, p<0.001) after PSM treatment. Multivariate logistic regression analysis showed that VE (p = 0.015, OR = 1.750, 95% CI = 1.115 to 2.746, E-value=2.90) and SA (p < 0.001, OR = 1.052, 95% CI= 1.030 to 1.074, E-value=1.29) were the predictors of IA. The model successfully classified 81.7% of cases overall (R 2 N = 0.133). Further analysis indicated that SA mediates between VE and IA (Z=3.644, p< 0.001).This study revealed the potential mediation effect of SA on the link between VE and IA.By acknowledging the mediating influence of SA, researchers and practitioners can develop more accurate and effective strategies to mitigate Internet Addiction among adolescents.